A bibliometric analysis of mental health trends among academicians in tertiary education / Siti Rosnita Sakarji, Abdul Kadir Othman and Siti Noraini Mohamad Tobi - Sakarji, Siti Rosnita; Othman, Abdul Kadir; Mohamad Tobi, Siti Noraini (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
Mental health issues among academicians are increasingly recognized as a global concern, attracting significant research attention in recent years. Academicians mental health affected due to increasing demands and lack of resources, resulting to the mental health issues such as depression, anxiety and stress. A bibliometric study analyzing publication trends on mental health among tertiary education academicians across various disciplines and national contexts highlights this growing focus. A systematic search of the Scopus database identified relevant articles from 2021-2024. The data shows a rise in publication output since 2020, with notable spikes during the COVID-19 pandemic, reaching 1269 papers which is 320 in 2021, 434 in 2022, 462 in 2023 and 53 in as of February 16, 2024. The analysis identifies the trends in mental health in tertiary education, the most prolific authors, top authors, popular keywords and the document by subject area. Highly cited articles focus on pandemic impacts, burnout, and the challenges of remote teaching. Frequently occurring keywords include mental health, stress, burnout, anxiety, and COVID-19, indicating the heightened attention these issues have received. The social sciences lead with 49% of the papers, followed by medicine (38%) and psychology (26%). Emerging fields like environmental science and computer science are contributing to the discourse. The findings underscore that heavy workloads, student interactions, and work-life imbalance are significant stressors negatively impacting academicians' mental health. This necessitates supportive interventions on stress management, mindfulness, and fostering healthy work cultures. Future research directions emphasize the importance of interdisciplinary collaboration, technology-enabled solutions, targeted interventions for specific academic groups, preventative strategies, and cross-cultural studies. The study reveals that as academician duties intensify, there is a pressing need for a coordinated international strategy to promote mental wellbeing among tertiary education staff. This global bibliometric review synthesizes key trends and establishes strategic priorities for both research and practice, offering a roadmap to proactively address the crucial yet understudied issue of mental health among academicians worldwide.